Exploring the hardness-independent wear behavior of typical wear-resistant materials under dynamic and static conditions - Shuai Wang; Xueyu Liao; Zhibin Zheng; Jun Long; Maolin Shen; Weixin Chen; Juan Wang; Dorob Berdiev; Kaihong Zheng (Journal of Materials Research and Technology)
In this study, three types of wear-resistant materials including high-chromium cast iron (HCCI), medium-chromium cast steel (MCCS), and low-chromium cast steel (LCCS), with similar macroscopic hardness but distinct microstructures and impact toughness have been prepared. The wear behavior of these three materials under different loads were investigated by impact wear experiments under dynamic load and three-body wear experiments under static load. The results revealed that the almost fully martensitised MCCS had the least mass loss under low dynamic impact load wear conditions. The brittleness associated with large carbides intensified with increasing impact load, culminating in a significant reduction in the impact wear resistance of HCCI. The residual austenite rapidly transformed into martensite, thereby effectively improving the wear resistance of the LCCS. Comparatively, the experimental steels were all characterized by fatigue wear of the abrasive on the material surface under static wear conditions at low loads and showed similar wear resistance. Conversely, the large carbides demonstrated superior wear resistance under conditions of high static load, and HCCI had the best wear resistance.